P08.30 Chlamydia tests ordered, but not undertaken: socio-demographic and structural barriers in general practice. (13th September 2015) - Lau, A; Spark, S; Tomnay, J; Temple-Smith, M; Fairley, CK; Guy, R; Donovan, B; Hocking, JS
Abstract : Introduction: Chlamydia screening at general practice clinics involves a general practitioner (GP) ordering a test and the patient providing a sample on-site or at a pathology collection centre off site. This study investigated the socio-demographic and structural factors associated with not providing a specimen for chlamydia testing when a test is requested by GP. Methods: Chlamydia testing data for 16 to 29 year old patients, including test requests and whether the test was performed, were collected from 63 GP clinics participating in a trial of a chlamydia testing intervention in Australia. The primary outcome was "no test performed" when a test was requested by a GP. Logistic regression was used to investigate factors associated with no test performed. Results: During the study period there were 13225 chlamydia test requests and of these, a chlamydia test was not performed for 2545 patients (19.2%; 95% CI: 16.5%, 22.3%). Multivariate analysis found that males (adjusted OR[aOR] = 1.4; 95% CI: 1.3, 1.6), those aged 16 to 19 years (aOR = 1.3; 95% CI: 1.1, 1.4), those living in areas of increasing socio-economic disadvantage (aOR = 1.2; 95% CI: 1.1, 1.4 for each additional quintile of Index of Relative Socio-economic Disadvantage) and those attending clinics that did not provide pathology collection onsite (aOR = 1.4; 95% CI: 1.0, 1.9) had an increased odds of not testing when a test was requested. Conclusion: One in five young people did not submit a specimen for chlamydia testing despite their GP requesting it. To capitalise on efforts in general practice to increase chlamydia testing, systems need to be introduced to minimise opportunities for patients to not provide a specimen. Disclosure of interest statement: This study was conducted as part of the Australian Chlamydia Control Effectiveness Pilot (ACCEPt) which has been funded by the Commonwealth Department of Health, NHMRC, NSW Health and the Victorian Department of Health.